(untitled) (American Journal of Pedagogical and Educational Research, 2023)
Every day around the world, a lot of information is rotat. This is due to the constantly growing technical capabilities of the Internet and mobile phones, people’s involvement in social networks and the year-on-year increase in Internet speeds. Today, as a result of a significant change in the digital sector, we can also monitor changes in the economy, finance and banking. At the same time, the people of our country make real-time card transfer (P2P) transactions, budgets, taxes, communal and other payments through mobile applications of digital banks, cooling loans, obtaining microorganisms and issuing online deposits, opening deposit and credit accounts remotely, conducting online currency conversion operations, and making payments from an international bank card account is making extensive use of enhancement and other remote banking services. To do this, it is possible to use banking services online remotely through a single bank application without the client coming to the bank building. Through this article, the digital bank (banking) itself provides information, what advantages there are between commercial banks and newly formed digital banks, their convenience for mankind, how the first digital banks in the world, the world and our country have an improved system of banking and financial processes, as well as their security. At the same time, we will stop the policy-making documents adopted in our country for the stability of the banking and financial system. "We intend to deepen reforms in banking and finance. The talk is about creating a healthy competitive environment in this area, actively attracting foreign banks to Uzbekistan, and fostering an effective stock market. We are very pleased to see our foreign partners invested in the banking sector in this hall. We are open to foreign investors’ proposals and initiatives aimed at further improving the banking and financial sector."—Shavkat Mirziyoyev 2022.